The effect of duality/non-duality of CEO, board size, meeting, committee on domestic shareholdings. - Sivathaasan, N.; Achchuthan, S. (Corporate Ownership and Control, 2014)
Purpose – This paper seeks to investigate the effect of duality/non-duality of CEO, board size, meeting, and committee on domestic shareholdings of manufacturing companies listed on Colombo Stock Exchange over a three-year period from 2011 to 2013. Research Design –The study employs the independent samples t-test, correlation and regression analyses to assess the relationships as well as the impact on domestic shareholdings using a sample of 32 quoted companies ( n =32). Findings –It is found that duality & non-duality of CEO structure do not differ in relation to domestic shareholdings that are inconsistent with the hypothesis formulated. Board size (+) and board meeting (+) have shown positive relationship and board committee (-) is negatively associated with domestic shareholdings. As per the empirical results, board committee and board size have significant (p < 0.05) impact on domestic share holdings and insignificant impact is observed by board meeting. Research Limitation -The present study concentrates only on the manufacturing sector quoted on Colombo Stock Exchange. Originality – This paper has taken an effort to this area of research on emerging share holdings held by local individuals and institutions in Sri Lanka and the findings could be generalized to the companies similar to this category.
Keywords: Duality/Non-Duality of CEO; Board Size; Board Meeting; Board Committee and Domestic Shareholdings